Yam and cowpea management by farmers in the Guinea-Sudan transition zone of Benin - ZANNOU, A. S. AFIO; Ahanchede, Adam; STRUIK, P. C.; RICHARDS, P.; ZOUNDJIHEKPON, JEANNE; Tossou, R.; VODOUHE, DAVO SIMPLICE (My University, 2004)
The maintenance and utilization of crop genetic diversity is important to ensure food security. The relative importance of yam and cowpea varieties and the influence of the socio-cultural and local economy context on the diversity maintained were analysed in Benin. Whereas the diversity is large, some varieties were rare, other ones on the way of being abandoned or already lost. Socio-cultural as well as economic and agronomic characteristics explained why some of them were still maintained. For example, the early-maturing yam variety Laboko was planted by most farmers to have tubers available in time for religious purposes, and some specific cowpea varieties played a role in the funeral of the parents in law. Farmers’ preferences were translated into criteria they use to appreciate varieties. The diversity of the varieties sold on the market and their availability over time reflect farmers’ strategies and conservation practices. The large price differences between varieties confirm the variation in quality as perceived by consumers. The most widely grown yam variety, Florido, is available on the market throughout the year but has a very low price. Market price differences among varieties are much smaller for cowpea than for yam. The processes of loss and displacement of some local varieties are described and the need for conservation is addressed. Different factors that may influence the level of varietal diversity in these crops, like the need to synchronize harvesting with high market prices, were analysed in depth. As opposed to mono-disciplinary approaches of scientists to farmers’ problems and constraints, farmers show an inter- or trans-disciplinary behaviour and express their preferences through multi-criteria processes.
Keywords: in situ conservation; farmer variety; agro-biodiversity; Dioscorea spp.; Vigna unguiculata; seed systems; market preference; research institution; learning process